FORMULATION AND IN VITRO CHARACTERISATION OF ATENOLOL TRANSDERMAL FILM WITH NATURAL POLYSACCHARIDE - GUPTA, SWARNIM; DAWN, RIMA; JANA, ABHISHEK; KAR, DEBARATI; ROY, TATHAGATA; DE, PINTU KUMAR (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of this research work targeted to create a mechanism for transdermal drug delivery containing atenolol with natural polysaccharide and modified natural polymeric combinations, using solvent evaporation technique and to analyse how polymers affect the transdermal patches physicochemical and drug-release characteristics. Methods: Solvent casting method has been used to formulate transdermal film. Chia seed mucilage (CSM), Carboxymethylated chia seed mucilage, Hydroxypropyl methylcellulose (HPMC) and Gelatin in different combination ratios were used as the polymer. Dibutyl phthalate was chosen as a plasticizer. Results: Result showed that the thickness of all film varied from 0.0546±0.0048 to 0.073±0.0032 mm with uniformity of thickness in each formulation. The average moisture content is found to be ranging between 4.8±0.13 to 5.67±0.14%. All batches had drug contents varying between 96 to 98 percent. All batches showed folding endurance grades exceeding 120. In comparison to formulation samples F1 to F4 (62.39%, 63.03%, 41.90%, and 23.68%, respectively), formulation samples F5 and F6 showed slower cumulative drug release of 35.26% and 34.27% at 480 min. Conclusion: According to the study’s findings, modifying the polymer has an impact on the transdermal film’s physicochemical and drug-release characteristics, and formulating an efficient transdermal film requires an optimum ratio of polymer to plasticizer combination. Higher proportion of modified polymer and plasticizer in the formulation of transdermal film, gives lower percentage drug release from prepared film. Thus, it can be concluded that the increase in the ratio of plasticizer and modified CSM polymer in comparison to unmodified CSM polymer will result in retarding drug release rate.